Seasonal Variation In Physico-Morphological And Functional Characteristics Of Semen Of Surti Buffalo Bulls And Their Interrelationships - Khawaskar, Megha V.; Panchal, M.T.; Dhami , A.J.; Patel , J.A. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
This study was carried out using 60 semen ejaculates (10 ejaculates/bull/season) obtained from 2 sexually mature healthy Surti buffalo bulls over one year p eriod. The year was divided in to three seasons (monsoon, winter and summer). The bulls were managed identically and were under weekly twice semen collection schedule in AV. The overall mean ejaculate volume, consistency/ density score (0-4), initial pH, mass activity (score 0-5), individual sperm motility, sperm concentration, live sperm, total abnormal sperm and sperm with intact acrosome recorded were 3.16±0.76 ml, 3.05±0.92, 6.89±0.16, 2.96±0.18, 71.66±12.37 %, 885.42±242.90 millions/ml, 85.75± 4.65 %, 6.53±1.28 % and 90.73±3.16 %, respectively. The average values for cold shock resistant sperm, hypo-osmotic swelling reactive sperm, and methylene blue reduction time were 53.45±8.30 %, 59.28±6.10 % and 7.11±1.28 minutes, respectively. The bulls varied significantly only in their ejaculate volume (P=0.008), sperm concentration (P=0.002) and live sperm (P=0.014). Seasonal influence was significant for ejaculate volume (P=0.002), density score (P=0.05), mass activity (P=0.002), sperm concentration (P=0.047), live sperm (P=0.001), abnormal sperm (P=0.003) and intact acrosome (P=0.022), cold shock resistant (P=0.000) and hypo-osmotic swelling reactive sperm (P=0.000). The lowest values were observed during winter for ejaculate volume, sperm concentration and live sperm, whereas density, mass activity and individual motility was the lowest during monsoon, and abnormal sperm, cold shock resistant sperm, HOS reactive sperm and MBRT during summer. The bull x season interaction was significant only for cold shock resistant sperm. Significant correlations were observed for ejaculate volume with cold shock resistant sperm (0.35); sperm concentration with live sperm (0.30) and MBRT (-0.31); mass activity with abnormal sperm (-0.26) and cold shock resistant sperm (-0.39); initial motility with live sperm (-0.27) and HOS reactive sperm (0.25); live sperm with HOS reactive sperm (-0.49) and cold shock resistant sperm (-0.56); abnormal sperm with intact acrosome (0.25) and cold shock resistant sperm (0.32); intact acrosome with HOS reactive sperm (0.37); and HOS reactive sperm with live sperm (-0.49) and cold shock resistant sperm (0.29).
Keywords: Buffalo semen; Seasonal Variation; Physical characteristics; Functional attributes